Phenotypic and Molecular Characterization of Erythromycin Resistance in Four Isolates of Streptococcus-Like Gram-Positive Cocci Causing Bacteremia - Woo, Patrick C. Y. (American Society for Microbiology, 2004)
Among nine patients with bacteremia caused by Granulicatella or Gemella in a 6-year period (July 1995 to June 2001), three had bacteremia caused by erythromycin-resistant Granulicatella adiacens and one had bacteremia caused by erythromycin-resistant Gemella haemolysans. All four isolates possessed mef genes, whereas none possessed ermT, ermTR, or ermB genes.